Copper/Zinc Superoxide Dismutase in Human Skin: Current Knowledge - Altobelli, Giovanna G.; Van Noorden, Susan; Balato, Anna; Cimini, Vincenzo (Frontiers in Medicine, 2020)
Superoxide dismutase is widespread in the human body, including skin and its appendages. Here, we focus on human skin copper/zinc SOD, the enzyme that protects skin and its appendages against reactive oxygen species (ROS). Human skin copper/zinc SOD resides in the cytoplasm of keratinocytes, where up to 90% of cellular ROS is produced. Factors other than cell type, such as gender, age and diseased state influence its location in skin tissues. We review current knowledge of skin copper/zinc SOD including recent studies in an attempt to contribute to solving the question of its remaining unexplained functions. The research described here may be applicable to pathologies associated with oxidative stress. However, recent studies on copper/zinc SOD in yeast reveal that its predominant function may be in signaling pathways rather than in scavenging superoxide ions. If confirmed in the skin, novel approaches might be developed to unravel the enzyme’s remaining mysteries.